Effects of denture adhesives on growth and morphological transformation of Candida albicans. Issue 1 (January 2020) - Nomura, Taro; Murakami, Tomohiko; Shimoyama, Yu; Kobayashi, Takuya; Furuya, Junichi; Sasaki, Minoru; Kondo, Hisatomo
Abstract: Purpose: We investigated the effects of denture adhesives (cream (Cr), powder (Po), and cushion (Cu)) on growth and adhesive-related morphological transformation of Candida albicans . For this purpose, the numbers of adherent C. albicans, hyphae-specific gene expressions, and the SEM images were examined. Methods: Acrylic resin blocks were prepared as controls (Co). Cr, Po, and Cu were thinly spread on the surface of the resin block. C. albicans suspension was seeded on the specimens and incubated at 4 °C for 2 h. The numbers of C. albicans adhering to each specimen at each incubation time period (1, 2, 3, 6, 12, and 24 h) were quantified using real-time RT-PCR. The hyphae-specific genes expressions were examined. The surface of each specimen was observed under the SEM to detect the transformation to the hyphal form. Results: The initial adhesion rates in all groups were not statistically significant. The numbers of C. albicans adhering increased with time in all groups, and those adhering to the Cr, Po, and Cu were significantly greater than that adhering to the Co. In the Cr and Po, the hyphal-specific genes expressions were higher after incubation for 6 h. The transformation to the hyphal form was identified in the Cr and Po after incubation for 6 and 12 h. Conclusions: The denture adhesives used in this study accelerated the growth of C. albicans . Moreover, the early transformation to the hyphal form on the Cr- and Po-type adhesives was observed, suggesting that we should carefully use Cr- and Po-type adhesives.